Spatial Analysis of Sumateran Elephant (Elephas maximus sumatranus) Movement in Giam Siak Kecil (GSK) Elephant Enclave, Riau - Hanifah Ikhsani; Eno Suwarno; Emy Sadjati; Muhammad Ikhwan; Tri Witanto (Universitas Muhammadiyah Palembang, 2024)
The Sumatran elephant is currently classified as critically endangered. A variety of conservation and conflict management initiatives have been implemented with the objective of reducing the intensity of conflict between elephants and humans. The use of GPS collars for monitoring purposes not only serves to reduce conflict but also allows for the continuous monitoring of Sumatran elephant movements. This study aims to analyze the spatial distribution and movement patterns of Sumatran elephants in GSK Elephant Pockets based on habitat factors, namely land cover class, slope, distance from rivers, and distance from roads. The research was conducted between December 2023 to June 2024 GSK Elephant Enclave, Riau. This study employed a multi-source approach to obtain data on the movement patterns of Sumatran elephants. These included data from the Sumatran Elephant GPS Collar, which recorded the animals' movements between 2021-2023. The movement characteristics analyzed include the length of the path traversed by the Sumatran elephant, Nearest neighbor classification was employed for the analysis of spatial distribution patterns. The result showed that spatial distribution pattern of Sumatran elephants in GSK Elephant Pockets 2021-2023 is clustered with an NNI of 0.47 (NNI < 1). The highest number of Sumatran elephant movements in 2023 based on habitat factors, namely land cover class, was in plantation forest, with 4,788 movements (82.23%). The next highest number of movements was in flat slope class, with 3,229 movements (55.45%). The distance from the river was 0–500 m, with 2,323 movements (39.89%), while the distance from the road was 0–500 m, with 5,390 movements (92.56%).